Epidemiology, clinical features, and outcome of the hospitalized patients with Kerion in Fars Province, Iran: an eleven-year retrospective study - Fateme Khosravi; Mohammad Mahdi Parvizi; Maryam Sadat Sadati; Mohammadreza Khosravi; Mehdi Ghahartars (BMC, 2024)
Abstract Background Kerion, a severe inflammatory type of tinea capitis, presents with purulent, boggy swelling and alopecia. Few articles in the literature provide information on this uncommon manifestation of tinea capitis (TC). This study aimed to determine the epidemiological and clinical characteristics of patients with Kerion over an 11-year period in an inpatient setting. Methods In this retrospective cross-sectional study, we enrolled all the admitted patients with inflammatory TC in the dermatology department of Shahid Faghihi referral hospital during 2011-2022. The data included demographic factors, animal contact, treatment, outcome, and past medical profiles. We used STATA 14.2 to analyze the data. Results One hundred and thirty-two patients with Kerion were enrolled in to the study. the mean age of patients was 7.6 ± 5.8 years. Boys (82.5%, n = 109) significantly outnumbered girls (17.5%, n = 23), and 82.2% of patients were under 11 years of age. Eight patients were one to two years old, two were infants under one year old, and five were adults. More than half (52.2%) of the patients were from rural areas. Most of the cases had heavily utilized systemic antifungal therapy, antibiotics, and corticosteroids. In addition, 43 patients reported positive animal contact. Over the course of an eleven-year period, there was a downward trend in the number of hospitalized patients. Conclusion We report one of the largest studies on Kerion patients over an eleven-year period. We have expanded the information on Kerion patients' epidemiology, transmission mode, and clinical outcomes. To develop preventative strategies for Kerion, future studies should focus on additional risk factors and individual susceptibilities.